Case Report: Response to ipilimumab and nivolumab in a patient with adrenocortical carcinoma - Charles, Rebecca; Madhu, Divine; Powles, Alexander; Boyde, Adam; Hughes, Owen; Kumar, Nagappan; Moorcraft, Sing Yu (Frontiers in Oncology, 2023)
Background: Adrenocortical carcinoma (ACC) is a rare malignancy with limited treatment options. The evidence for the use of immunotherapy in ACC has been conflicting, with overall response rates ranging from 6 -33%.We describe the case of a 32 year old patient who was initially thought to have an inoperable clear cell renal cell carcinoma and was treated with immunotherapy with ipilimumab and nivolumab. The patient had an excellent partial response to treatment. Further work-up prior to consideration of surgery demonstrated that the tumour was an ACC, rather than a renal cancer. She had a right adrenalectomy and right hepatectomy, achieving an R0 resection and remains disease-free one year after surgery.This case illustrates the challenge of diagnosing ACC, and that doublet immunotherapy with ipilimumab and nivolumab can have significant clinical efficacy in ACC.